Fundamentalisme Islam: Kecenderungan antara Menafsirkan Realitas dan Doktrin - Aden Wizjan SZ (Universitas Islam Indonesia, 2002)
The article below tries to describe the position of the fundamentalism of Islam as the trend between understanding the realities of religion followers and interpreting the doctrine of religion. Actually the term